2015
DOI: 10.1542/peds.2015-0080
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Genotype and Sleep on Temperament

Abstract: , on behalf of the MAVAN research team abstract BACKGROUND AND OBJECTIVES: Sleep problems are frequent in young children; however, children vary in the degree to which they are affected by poor sleep quality. We investigated whether a polymorphism in the serotonin transporter gene, which is linked to emotional function, is a potential moderator of the influences of sleep duration on infant temperament using longitudinal data. METHODS:We examined the interactive effects of average sleep duration between 6 and 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 48 publications
0
12
1
Order By: Relevance
“…In other words, individual variability in sleep-wake behaviour problems has been linked to affect and emotions through hypothesised shared central nervous system to sleep and the neurobehavioural systems underlying arousal and emotions 31 32. In accordance with this assumption, difficult temperament33 and genetic factors34 are related to both sleeping and emotional problems in children. Second, sleep and emotional problems may be explained by the same environmental factors.…”
Section: Discussionmentioning
confidence: 93%
“…In other words, individual variability in sleep-wake behaviour problems has been linked to affect and emotions through hypothesised shared central nervous system to sleep and the neurobehavioural systems underlying arousal and emotions 31 32. In accordance with this assumption, difficult temperament33 and genetic factors34 are related to both sleeping and emotional problems in children. Second, sleep and emotional problems may be explained by the same environmental factors.…”
Section: Discussionmentioning
confidence: 93%
“…() found in their study that treatment of sleep disturbance improved daytime behaviour. New findings also report a differential role of sleep according to the child's genotype (Bouvette‐Turcot et al ., ). Our present understanding in this field could be greatly improved by these innovative research approaches.…”
Section: Discussionmentioning
confidence: 97%
“…Effects of sleep-wake behaviour were less studied, but worse sleep-wake behaviour were shown to predict later social-emotional (Bernier et al, 2010;Bordeleau et al, 2012;Bouvette-Turcot et al, 2015;Sadeh et al, 2015;Saenz et al, 2015), and sleep problems (Byars et al, 2012;Hysing et al, 2014;Palmstierna et al, 2008;Tikotzky & Shaashua, 2012).…”
Section: Factors Positively and Negatively Affected By Sleep-wake Behmentioning
confidence: 99%
“…This may indicate that early sleep-wake behaviour is associated with brain maturation (Saenz et al, 2015). Authors of a recent study stated the importance of differential susceptibility in the association between sleep duration and later emotional development, reporting that this association is only present in infants with 5-HTTLPR allele (Bouvette-Turcot et al, 2015). Sleep-wake behaviour was not associated with externalizing problems in 1 study, whose results suggested, however, that sleep duration during the night moderated the association between maternal sensitivity and internalizing/externalizing symptoms (Bordeleau et al, 2012).…”
Section: Factors Positively and Negatively Affected By Sleep-wake Behmentioning
confidence: 99%